Mass-media as a source of new phraseology in modern Ukrainian literary language - Syzonov, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2017)
The article is focused on the role of mass media in updating of modern Ukrainian language. Mass media of various types – printed, digital and advertising - have become the basis of the research. The author presents a comprehensive analysis of extra- and intralingual characteristics which influence on the phraseological systems’ update. The following issues have been considered in the article: linguistic imperialism, theory of linguistic economy, world globalization processes, rise of new platforms which influence on innovative processes. Based on the collected material, the author suggests a classification of new phraseological units depending on frequency of their usage in the media. It has been proved that creation of new phraseological units in the mass media is connected with their key functions, namely to inform the recipient and influence on him, name and construe new phenomena and create a verbalized image by different stylistic tools.